Medições de ruído em simultaneo por diferentes equipamentos e suas implicações legais - Pereira, Liliana; Neves, Miguel; Carrana, Pedro; Pais, Rui (My University, 2019)
In the ambit of the evaluation of security and health conditions of the workers of the management systems of RSU is essential the knowledge and the control of the existing risks that are associated to the various activities executed and developed during the day in the different working shifts by workers of undifferentiated residual collection, selective collection and landfill. In this way, the present work had as its objective, yet to carry out a whole measure of simultaneous noise readings with a sound level meter and dosimeter to identify possible differences of the values between the measurements. These measurements intend to place some questions which are the following: whit the obtained results in the measurements can one verify possible alterations of legal obligations on the part of the firms?; are there verified differences in the measurements results with sound level meter and dosimeter?; the differences found may be significant to the point of altering more than the legal obligation?
Simultaneous noise measurements by different equipment and their legal implications
Keywords: Noise; Sound level meter; Dosimeter; Measure; Comparison of legal obligation